ANALISIS FAKTOR YANG MEMENGARUHI KEPUTUSAN PEMBELIAN PRODUK HALAL DIMEDIASI SERTIFIKASI HALAL PADA MASYARAKAT MUSLIM JABODETABEK - Zikry Ramadhan (2023)
There have been many food and beverage products circulating among the muslim community but this distribution has not been followed by halal certification of their products. Considering that the majority of the population in Indonesia is a muslim, this needs to be a concern so that new products that are widely circulated can be consumed safely in accordance with Islamic law. This study aims to analyze how much influence the results of religiosity, viral marketing, and prices have on purchasing decisions for halal products for the Jabodetabek muslim community through halal certification as a mediating variable. This research method is quantitative involving 174 respondents using non-probability sampling and purposive sampling as the method. This study uses primary data collected through a google form questionnaire that is distributed via social media. Analysis technique using SEM-PLS via SmartPLS software. Research findings confirm that religiosity and viral marketing have a significant effect on the direct purchase decision of halal products, while price does not have a significant effect on the direct purchase decision of halal products. For testing halal certification as mediation is not able to mediate the relationship between the variables of religiosity, viral marketing, and price on purchasing decisions of halal products indirectly. The limitations of this study are the lack of references discussing halal certification as a mediating variable, the variables used are still limited to three independent variables, and the respondents obtained are still dominated by students and generation Z. For further research it is advisable to use independent variables other than those used in this study and embrace other respondents from the general public.